An unreliable retrial queue with delaying repair and general retrial times under Bernoulli vacation schedule - Choudhury, Gautam; Ke, Jau-Chuan (Applied mathematics and computation, 2014)
This paper deals with the steady state behavior of an M/G/1 queue with general retrial time and Bernoulli vacation schedule for an unreliable server, which consist of a breakdown period and delay period. While the server is working with primary customers, it may breakdown at any instant and server will be down for short interval of time. Further concept of the delay time is also introduced. The primary customer finding the server busy, down or vacation enters a group of unsatisfied customer called orbit. After the completion of a service, the server either goes for a vacation of random length with probability p or may continue serve for the next unit, if any with probability (1−p). For this model, we first derive the system size distribution at a departure epoch. Secondly, we derive the probability generating function of joint distributions of state of the server and queue size, which is one of chief objectives of the paper. Finally, we obtain some important performance measures and reliability indices of this model.